Uma história do piano em São Luís do Maranhão - SILVA, Paula Figueirêdo da (2013)
Dissertation consists of a historical survey about the musical and piano education in Sao Luis. In the first chapter, it is pointed out musical education in Brazil as a whole, since the first music educators, the Jesuits, through the arrival of the piano to Brazil in the 19th century, the latest legislative changes on the implantation of music in schools. On the Second moment the research focuses on the specific study of the evolution of the piano teaching in São Luis, seeking to understand the context of the ludovicense society when this instrument was welcomed in the early 19th century, and reflecting on the role that it represented in the social context. In the third chapter it investigates the first half of the 20th century, gathering bibliographic information from the major pianists and piano teachers from the city in an attempt to know and record data about those who made the history of the piano in São Luis, in which until 1974 there was not a public institution of instrumental teaching. In the last chapter it analyzes the School of Music of the State of Maranhão, where it is organized information about piano teachers and graduates, as well as raised discussions about the institution, main school that forms pianists in São Luis.